B-vitamin Mixture Improves the Analgesic Effect of Diclofenac in Patients with Osteoarthritis: A Double Blind Study - Magaña-Villa, M. C.; Rocha-González, H. I.; Fernández del Valle-Laisequilla, C.; Granados-Soto, V.; Rodríguez-Silverio, J.; Flores-Murrieta, F. J.; Carrasco-Portugal, M. C.; Reyes-García, J. G. (Drug Research, 2013)
According to the high consumption of the mixture of B vitamins and diclofenac in several countries, this combination has constituted a frequently used option in pain therapy from inflammatory origin. Although the evidence obtained from inflammatory pain animal models has shown the existence of analgesic synergy between diclofenac and the B vitamins mixture, the corresponding clinical evidence is scarce. A double-blind, randomized clinical trial study was designed to characterize the analgesic effect and safety of diclofenac and B vitamins against diclofenac alone in patients with severe osteoarthritis. Forty eight patients programmed to total knee arthroplasty with a pain level ≥7 in a 1–10 cm visual analogue scale were allocated to receive a single intramuscular injection of sodium diclofenac (75 mg) alone or combined with thiamine (100 mg), pyridoxine (100 mg) and cyanocobalamin (5 mg), and the pain level was evaluated during 12 h post-injection. Diclofenac+B vitamins mixture showed a superior analgesic effect during the assessed period and also a better assessment of the pain relief perception by patients than diclofenac alone. This study constitutes a clinical support on the improvement of the analgesic effect of diclofenac by B vitamins in patients with osteoarthritis programmed to total knee arthroplasty, as a clinical model of inflammatory pain.
Keywords: analgesia; osteoarthritis; B vitamins; diclofenac; inflammatory pain